Beyond exposure‐response: A tutorial on statistical considerations in dose‐ranging studies - Glen Laird; Lei Xu; Meng Liu; Jin Liu (Wiley, 2021)
Abstract Dose‐ranging studies are a crucial part of the phase II drug development process. They complement the understanding gained from exposure‐response analyses. However, the statistical design issues related to dose‐ranging studies are not always keenly understood and a poorly designed study can be costly for later development. In this tutorial, we review five key statistical principles in designing such a study. We also describe some popular statistical approaches, including pairwise comparison, modeling, and Multiple Comparison Procedure modeling in the context of principles.